EFFICIENT MARKETING CHANNELS AS PREREQUISITE FOR COMPETITIVENESS IN THE SERBIAN GAS BOILER MARKET - Jovičić, Dragoljub; Vranješ, Marija; Gašević, Dragana (International Journal of Economic Practice and Policy, 2019)
In the last ten years, the Serbian gas boiler market has been intensively developing. Along with the increase in demand, the number of present brands increased, as well as the number of distributors who were engaged in the placement of products. Competition has become sharper, and only those distributors who had an efficient marketing mix could have a competitive advantage and provide survival on the Serbian market. In order to explore the importance of individual marketing mix instruments in placement of gas boilers in Serbia, authors preliminarily interviewed customers, experts - technical persons, sales managers, as well, who may well know this very complex problem. The research was based on a research hypothesis that reads: Efficient marketing channels represent a key factor for achieving competitive advantage in the Serbian gas boiler market. After field research, the collected data are processed by using appropriate methodology and the results of the survey confirmed the research hypothesis.
Keywords: Serbian gas boiler market; marketing mix; competitiveness; marketing channels